Cordão Formation: loess deposits in the southern coastal plain of the state of Rio Grande do Sul, Brazil - LOPES,RENATO P. (2016)
ABSTRACT Loess consists of silt-dominated sediments that cover ~10% of the Earth's surface. In southern South America it occurs in Argentina, Bolivia, Paraguay and Uruguay, and its presence in southern Brazil was never studied in detail. Here is proposed a new lithostratigraphic unit, Cordão Formation, consisting of loess deposits in the southern Brazilian coastal plain. It consists of fine-very fine silt with subordinate sand and clay, found mostly in lowland areas between Pleistocene coastal barriers. These sediments are pale-colored (10YR hue) and forms ~1,5-2,0 meter-thick stable vertical walls. The clay minerals include illite, smectite, interstratified illite/smectite and kaolinite, the coarser fraction is mostly quartz and plagioclase. Caliche and iron-manganese nodules are also present. The only fossils found so far are rodent teeth and a tooth of a camelid (Hemiauchenia paradoxa). Luminescence ages indicate that this loess was deposited in the latest Pleistocene, between ~30 and 10 kyrs ago, and its upper portion was modified by erosion and accumulation of clay and organic matter in the Holocene. The estimated accumulation rate was ~630 g/m2/year. The probable source of this loess is the Pampean Aeolian System of Argentina and it would have been deposited by the increased aeolian processes of the last glacial.